Expression of Oncofetal Antigen 5T4 in Murine Taste Papillae - Takahashi, Yuka; Takahashi, Hiroo; Stern, Peter L.; Kirita, Tadaaki; Tsuboi, Akio (Frontiers in Cellular Neuroscience, 2019)
BACKGROUND: Multicellular taste buds located within taste papillae on the tongue mediate taste sensation. In taste papillae, taste bud cells, such as taste receptor cells and taste precursor cells, and the surrounding lingual epithelium including epithelial progenitors (also called taste stem/progenitor cells) are maintained by continuous cell turnover throughout life. However, it remains unknown how the cells constituting taste buds proliferate and differentiate to maintain taste bud tissue. Based on in situ hybridization screening, we demonstrated that the oncofetal antigen 5T4 (also known as trophoblast glycoprotein: TPBG) gene is expressed in the adult mouse tongue. RESULTS: In immunohistochemistry of coronal tongue sections, 5T4 protein was detected at a low level exclusively in the basal part of the lingual epithelium in developing and adult mice, and at a high level particularly in foliate papillae and circumvallate papillae (CVPs). Furthermore, immunohistochemistry of the basal part of CVPs indicated that the proliferation marker PCNA (proliferating cell nuclear antigen) co-localized with 5T4. 5T4 was strongly expressed in Krt5+ epithelial progenitors and Shh+ taste precursor cells, but weakly in mature taste receptor cells. The number of proliferating cells in the CVP was higher in 5T4-knockout mice than in wild-type mice, while neither cell differentiation nor the size of taste buds differed between these two groups of mice. Notably, X-ray irradiation enhanced cell proliferation more in 5T4-knockout mice than in wild-type mice. CONCLUSIONS: Our results suggest that 5T4, expressed in epithelial progenitors (taste stem/progenitor cells) and taste precursor cells, may influence the maintenance of taste papillae under both normal and injury conditions.